Strategi Peningkatan Mutu Pendidikan Islam - M. Asep Fathur Rozi (Tarbiyah Departement collaboration with AMCA, 2016)
The development of human resources influenced the quality of educational institutions.The quality of educational institutions influenced by vision and mission the agency. The formulation of vision and mission institutions involving stakeholders already set by the institutions. A factor causing the quality of education not been successful among others, strategy education is input oriented and management of education has been is macro-oriented. After the preparation of vision and mission, institutions formulate strategic plan. Strategy is important policy of the as the basis of in making institutional program. Business could be undertaken by educational institutions to improve the quality of institutions, among other: prepared leader who quality, formulate vision and mission with a characteristic wholly owned by intitusi, formulate strategy in an effort to create the purpose of institutions, improve the ability of human resources, conducted a survey market, furnish facilities and infrastructure, financial management, to improve cooperation with the stakeholders, tending consistency quality.